Characteristics and Clinical Outcomes in Antiretroviral Treated HIV-HBV Co-infection - Rana, Urvi (Université d'Ottawa / University of Ottawa, 2018)
Objective: The objective of this thesis was to compare demographic and clinical characteristics and factors associated with advanced hepatic fibrosis between HIV and HIV-hepatitis B (HBV) co-infected patients. Methods: Proportional odds models were developed to investigate socio-demographic and clinical variables’ association on liver fibrosis determined by AST-to-Platelet-Ratio-Index (APRI). Results: HBV status and APRI values were available for 2,419 of 9,289 (26%) participants. 199 (9%) were HBV co-infected. Compared to HIV infected, HIV-HBV co-infected individuals were 2.19 (95% CI: 1.63, 2.90) and 1.68 (95% CI: 1.10, 2.53) times more likely to belong in a higher level of APRI category. Compared to HIV mono-infection, HIV-HBV co-infected participants on ARV therapy were less likely to have clinically significant or advanced fibrosis compared to mild or moderate fibrosis. Conclusion: We provide evidence in favour of an association between ARV therapy and reduced fibrosis in HIV-HBV co-infected population.
Keywords: HIV; HBV; Co-infection; CANOC